2005
DOI: 10.1176/appi.ps.56.8.927
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Concurrent Depression and Anxiety and Six-Month Outcome of Addiction Treatment

Abstract: Concurrent depression or anxiety symptoms at intake had a small but significant predictive effect on addiction treatment outcome over and above factors that are clearly known to influence outcome (length of stay in treatment and initial addiction severity).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 39 publications
3
43
0
4
Order By: Relevance
“…Meanwhile, patients with low psychiatric severity showed the most improvement, regardless of treatment modality, and treatment outcome for patients with moderate psychiatric severity varied according to patient-treatment characteristics. More recent studies have replicated these findings, with higher psychiatric severity associated with poorer outcome (Charney et al, 2005;Compton et al, 2003;Greenfield et al, 1998). Psychiatrically ill participants in these studies were likely to drop out of treatment earlier and relapse to substance use sooner than less psychiatrically ill participants.…”
Section: Introductionmentioning
confidence: 62%
“…Meanwhile, patients with low psychiatric severity showed the most improvement, regardless of treatment modality, and treatment outcome for patients with moderate psychiatric severity varied according to patient-treatment characteristics. More recent studies have replicated these findings, with higher psychiatric severity associated with poorer outcome (Charney et al, 2005;Compton et al, 2003;Greenfield et al, 1998). Psychiatrically ill participants in these studies were likely to drop out of treatment earlier and relapse to substance use sooner than less psychiatrically ill participants.…”
Section: Introductionmentioning
confidence: 62%
“…Psychiatric conditions are highly prevalent among individuals with SU problems (Alaja et al 1998;Harris and Edlund 2005;Kessler et al 1996;Mendelson et al 1986;Moos, Brennan, and Mertens 1994), and research has found that interventions directed at psychiatric problems during chemical dependency (CD) treatment lead to improved treatment outcomes (Chi, Satre, and Weisner 2006;McLellan et al 1993;Ray, Weisner, and Mertens 2005;Saxon and Calsyn 1995). Psychiatric severity is also a well-established predictor of SU outcomes, quality of life, and subsequent health status (Charney et al 2005;Friedmann et al 2003;Moos, Nichol, and Moos 2002;Ray, Weisner, and Mertens 2005;Ritsher et al 2002;Schaar and Ojehagen 2003).…”
Section: Abstract Longitudinal Substance Use Outcomes; Psychiatric Trmentioning
confidence: 99%
“…The lifetime prevalence rates of major depression in the general population are notable, with rates ranging from 13-16% (Kessler et al 2003;Hasin et al 2005), while the rates of major depression in treatment-seeking cocaine abusers are higher, with rates ranging from 15-30% (Rounsaville and Carroll 1991;Kilbey, Breslau and Andreski 1992;Charney et al 2005;McLean et al 1999). Similarly, Kessler et al (2006) found that the rate of adult ADHD in the U.S. population is 4.4%, whereas recent prevalence studies in substance dependent samples seeking treatment have obtained rates ranging from 15-24% (Levin, Evans and Kleber 1998;King et al 1999;Schubiner et al 2000), suggesting that these disorders merit clinical attention in substance abuse treatment settings.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies show major depression, or psychiatric severity in general, to be associated with poorer substance use outcome or treatment retention (Rounsaville et al 1986;Kosten, Rounsaville and Kleber 1987;Rounsaville et al 1987;Carroll et al 1993;Hasin et al 2002;Greenfield et al 1998;Charney et al 2005;Dodge, Sindelar and Sinha 2005), whereas other studies suggest that there is no negative impact on treatment retention or perhaps even a positive impact of depression on retention in treatment Agosti, Stewart and Quitkin 1991;McKay et al 2002;Siqueland et al 2002;Brown et al 1998). In one review of this literature, Hasin and colleagues (2004) conclude that major depression tends to confer a poor prognosis, while the impact of depressive symptoms, measured with cross-sectional scales, is less clear.…”
Section: Introductionmentioning
confidence: 99%